Essential Visual J++ 6.0 fast : How to develop Java applications and applets with Visual J++ - Cowell, John (Brown, Carl, 1946- Essential series., 1999)
Java is an object oriented language which allows you to create interactive Web pages, or to write applications which will run on any computer. Visual J++ gives you access to the power of Java with all the benefits of a modern visual development environment, for fast programming, and debugging. If you are new to Java or are an existing Java programmer who wants to switch to Visual J++, this book gives you all the essential information you need using lots of examples. Topics covered in this book include: the Java language, polymorphism, inheritance and encapsulation, graphics and animation, handling events, using files, exception handling, abstract windowing toolkit, the Java applet wizard and the resource wizards, debugging, and project management. Essential Visual J++ 6.0 fast is designed for professional developers or students who need to learn the maximum in the minimum time and to develop applications fast.